Praktik Pembelajaran Inklusi dan Integratif dalam Mata Pelajaran PAI - Sulaiman Sulaiman; Hizbul Muflihin (Universitas Muhammadiyah Jember, 2021)
Children with special needs are children who have weaknesses in vision or in thinking, thereby making them different from others. These children need assistance that allows comfortable learning, special services, specific learning methods and assistance so that these children experience development and change as well as can live independently. That is, when these children are facilitated with complete learning media, they will be capable of understanding scientific knowledge, even though they are different from children in general. This study will examine the practice of inclusive and integrative learning at schools. Researchers will take a case study at SD Putra Harapan Bantar, West Purwokerto. This study employs a qualitative descriptive approach by describing and interpreting the condition of the situation and according to the reality in the field related to the practice of integrative inclusive learning at the Putra Harapan Primary School Bantarsoka Purwokerto Barat. The data collection techniques are interviews, observation, and documentation. The data analysis technique used by the researcher is the Flow model, which includes data reduction, and drawing conclusions. The subjects in this study are principals, students, teachers and others. while the object of this research is the practice of inclusive and integrative learning at the Putra Harapan Bantarsoka Elementary School, West Purwokerto District. The results obtained by the researcher are that the Putra Harapan Bantarsoka Elementary School, Purwokerto Barat is a Fulday school and the learning materials are more than those exist in many schools in general, such as congregational prayer dhuhur prayer, dhuha prayer, brushing teeth, washing dishes, practicing ablution, eating snacks together. There are three subject matter services delivered at SD Putra Harapan, namely intensive classes, transition classes, and special needs students.